2018
DOI: 10.1371/journal.pone.0194616
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of Fusarium graminearum reveals signatures of divergent evolution within a major cereal pathogen

Abstract: The cereal pathogen Fusarium graminearum is the primary cause of Fusarium head blight (FHB) and a significant threat to food safety and crop production. To elucidate population structure and identify genomic targets of selection within major FHB pathogen populations in North America we sequenced the genomes of 60 diverse F. graminearum isolates. We also assembled the first pan-genome for F. graminearum to clarify population-level differences in gene content potentially contributing to pathogen diversity. Bayes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 133 publications
2
76
0
Order By: Relevance
“…Desjardins (2006) has showed that there exists trichothecene-nonproducing mutant of F. graminearum; however, we found that in the FDG samples DON concentrations averaged 7620 µg kg -1 . This suggests that FDG is much more dangerous due to possible higher concentrations of DON compared to BDG (Lowe et al, 2012;Kelly, Ward, 2018). In the welldried wheat grain samples with BDG, the concentrations of DON were below the limit of detection.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Desjardins (2006) has showed that there exists trichothecene-nonproducing mutant of F. graminearum; however, we found that in the FDG samples DON concentrations averaged 7620 µg kg -1 . This suggests that FDG is much more dangerous due to possible higher concentrations of DON compared to BDG (Lowe et al, 2012;Kelly, Ward, 2018). In the welldried wheat grain samples with BDG, the concentrations of DON were below the limit of detection.…”
Section: Resultsmentioning
confidence: 98%
“…Cereals are a primary source of a human diet, with wheat being the third most produced grain worldwide. The cereal-infecting species Fusarium graminearum (teleomorph Gibberella zeae), F. culmorum and F. pseudograminearum produce a range of type B trichothecenes, including deoxynivalenol (DON) and its acetylated derivatives, which inhibit protein translation in eukaryotes that are known virulence factors on wheat (Kelly, Ward, 2018). Fusarium graminearum (sexual stage Gibberella zeae) is the causal agent of head blight of common wheat (Triticum aestivum L.).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel type A trichothecene mycotoxin (NX‐2), which is very similar in structure to 3DON, was detected in F. graminearum isolates in midwestern USA (Liang et al , ; Varga et al , ) and in southern areas of both eastern and western Canada (Kelly et al , ). These NX‐2‐producing isolates are now recognized as the NA3 population (Kelly and Ward, ). In planta, NX‐2 is converted into a deacetylated derivative, NX‐3, which has the same capacity as DON to inhibit eukaryotic protein synthesis (Varga et al , ).…”
Section: Emergence Of Residue‐borne Diseases: Fhbmentioning
confidence: 99%
“…The NA3 isolates are genetically distinct from NA1 and NA2, and have high genetic diversity. Their restricted existence in northern USA and southern Canada is probably due to an endemic origin of these isolates exclusively in this part of the world (Kelly and Ward, ).…”
Section: Emergence Of Residue‐borne Diseases: Fhbmentioning
confidence: 99%
See 1 more Smart Citation